Digital Media Management Through Photography And Videography - Moh Robit Aufalmuna; Eka Diana (FASHLUNA, 2026)
This study examines the management of digital media through photography and videography as a strategy to improve literacy at MI Raudlatul Hasaniah. The study aims to explore how digital media, particularly visual media, are integrated into the curriculum, how roles are distributed within the school for their implementation, and how the effectiveness of this integration is evaluated. A qualitative case study approach was used, involving in-depth interviews with school administrators, teachers, and students, as well as participatory observation and document analysis. The findings indicate that MI Raudlatul Hasaniah successfully integrated visual media into the curriculum through a structured process that clearly divided roles among staff, including teachers, IT staff, and media coordinators. The implementation of visual media, particularly photos and videos, in the classroom has increased student engagement and their understanding of abstract concepts in subjects such as mathematics, science, and civic education. The effectiveness of these media was evaluated through continuous student and teacher feedback and periodic assessments. The results demonstrate a positive impact on students’ understanding and engagement in lessons, indicating that the integration of digital media contributes positively to student engagement and literacy development.